Investigating the potential of oxidative stress-related gene as predictive markers in idiopathic pulmonary fibrosis - Yuhao Wang; Zhao Zhang; Hongnan Zhang; Luyao Xu; Shuling Huang; Ying Wen; Zhiming Zhuang; Xiaoxin Li; Jinyi Lu; Xudong Li (Scientific Reports)
Abstract This study investigates genes linking oxidative stress to idiopathic pulmonary fibrosis (IPF) through multi-omics data integration. We collected oxidative stress-related genes from GeneCards and integrated data for gene expression (eQTLs), DNA methylation (mQTLs), and protein expression (pQTLs). Genome-wide association study (GWAS) data on IPF from Allen et al. served as the discovery set, with FinnGen R10 for validation. Summary data-based Mendelian randomization (SMR) and colocalization analyses assessed interactions and shared causal variants, followed by multi-omics integration with tissue-specific validation. SMR and colocalization screening identified 90 mQTLs, 15 eQTLs, and 2 pQTLs (KRT18 and FOXO1) linked to IPF in the discovery cohort. Twelve mQTLs were validated in the FinnGen cohort, with MUC1 showing strong SMR and colocalization evidence (eQTL). Multi-omics integration validated NDUFA9 (mQTL-eQTL) level and FOXO1 (mQTL-eQTL-pQTL). Our study identified key oxidative stress-related genes (i.e., FOXO1 and NDUFA9) in IPF pathogenesis, highlighting the need for further research to inform prevention and treatment.